2022
DOI: 10.1152/ajpendo.00247.2021
|View full text |Cite
|
Sign up to set email alerts
|

Regenerating myofiber directs Tregs and Th17 responses in inflamed muscle through the intrinsic TGF-β signaling-mediated IL-6 production

Abstract: TGF-β is considered to be an important immuno regulatory cytokine. However, it remains unknown whether and how the muscle fiber specific-TGF-β signaling is directly involved in intramuscular inflammatory regulation by affecting T cells. Here, we addressed these in a mouse tibialis anterior muscle Cardiotoxin injection-induced injury repair model in MCK-Cre control or transgenic mice with TGF-β receptor II (TGF-βr2) being specifically deleted in muscle cells (SM TGF-βr2-/-). In control mice, TGF-β2 and TGF-βr2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 54 publications
1
10
0
Order By: Relevance
“…Our recent work proved that deficiency of TGF-β signaling in muscle cells caused more serious infiltration of macrophages and CD4 T cells at the degeneration stage (D4) and the early stage of regeneration (D7) after myoinjury [ + 26 ]. To further clarify this, the inflammatory response was evaluated using muscle TGF-βr2 deficient mice (SM TGF-βr2 −/− mice), which were hybridized from TGF-βr2-floxed mice and MCK-Cre mice (Additional file 2 : Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Our recent work proved that deficiency of TGF-β signaling in muscle cells caused more serious infiltration of macrophages and CD4 T cells at the degeneration stage (D4) and the early stage of regeneration (D7) after myoinjury [ + 26 ]. To further clarify this, the inflammatory response was evaluated using muscle TGF-βr2 deficient mice (SM TGF-βr2 −/− mice), which were hybridized from TGF-βr2-floxed mice and MCK-Cre mice (Additional file 2 : Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To further clarify this, the inflammatory response was evaluated using muscle TGF-βr2 deficient mice (SM TGF-βr2 −/− mice), which were hybridized from TGF-βr2-floxed mice and MCK-Cre mice (Additional file 2 : Fig. S1) [ 26 ]. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have shown that the inflammatory environment induced by interferon gamma (IFN-γ) stimulates the expression of major histocompatibility complex (MHC) and some co-stimulatory molecules from regenerated myofibers or cultured myoblasts and myotubes, which then contribute to the immune response [ 98 ]. Myofibers also mediate the inflammatory response through the activation of transforming growth factor beta (TGF-β)/IL-6 signaling, and direct Th17 and Treg cell responses [ 99 ]. Moreover, oxidative stress during the inflammatory response can also change the structure and function of proteins, which then regulates muscle regeneration in CTX-induced injury [ 100 ].…”
Section: Mechanisms Of Regeneration In Ctx-induced Injury Modelsmentioning
confidence: 99%